Stable single device multi-pore electrospraying of polymeric microparticles via controlled electrostatic interactions. Issue 107 (15th October 2015) - Zhang, Chunchen; Chang, Ming-Wei; Ahmad, Zeeshan; Hu, Weiwen; Zhao, Ding; Li, Jing-Song
Abstract : A novel flute-like multi-pore electrospray emitter was designed and manufactured to enable economical scale-up smooth spherical microparticles. The effect of processing parameters and device configuration on particle sizes is described. Abstract : This work demonstrates a facile fabrication method to produce high throughput biodegradable microparticles (MPs) using a flute-like multi-pore emitter device in place of conventional single needle electrospraying capillaries. By manipulating the configuration of the emitter and the processing parameters, uniform microparticles are successfully sprayed in a single step for large-scale production. Furthermore, by manipulating individual spatial pore location various jet-bending interactions, which give rise to particle variations and irregularities, are overcome. Finally, findings correlate well with models reported by Hartman.